2010
DOI: 10.1002/cncr.25145
|View full text |Cite
|
Sign up to set email alerts
|

Detection of minimal residual disease in blood and bone marrow in early stage breast cancer

Abstract: BACKGROUND:The significance of circulating tumor cells (CTCs) in blood and of disseminated tumor cells (DTCs) in bone marrow (BM) in patients with early stage breast cancer is unclear. In this study, the authors investigated the occurrence of CTCs and DTCs in women with early stage breast cancer and evaluated the correlation of their presence with other prognostic markers. METHODS: Blood and BM aspirations were collected at the time of primary breast surgery. CTCs were detected by using the CellSearch assay, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
71
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 16 publications
13
71
1
1
Order By: Relevance
“…Although both CTCs (10% of the patients) and DTCs (14% of the patients) were significantly associated with worse clinical outcome, DTCs were more informative than CTCs [61]. Th is and other studies [62] showed that there was no good correlation between CTC and DTC detection. However, it is not clear whether this is because CTCs and DTCs represent diff erent tumor cell populations or whether this is also related to limitations of the detection technologies used.…”
Section: Ctcs Versus Dtcsmentioning
confidence: 79%
“…Although both CTCs (10% of the patients) and DTCs (14% of the patients) were significantly associated with worse clinical outcome, DTCs were more informative than CTCs [61]. Th is and other studies [62] showed that there was no good correlation between CTC and DTC detection. However, it is not clear whether this is because CTCs and DTCs represent diff erent tumor cell populations or whether this is also related to limitations of the detection technologies used.…”
Section: Ctcs Versus Dtcsmentioning
confidence: 79%
“…Between 20–30% of patients with no clinically detected metastasis have been observed to be positive for CTCs in several studies [24, 41, 42]. However, the low sensitivity of current CTC identification tests in early breast cancer is a significant impediment to their use as screening tools to diagnose breast cancer.…”
Section: Role Of Ctcs In Localized Breast Cancermentioning
confidence: 99%
“…What role does time of sampling, amount of sample drawn or individual patient characteristics have on the quality of the assay, are a few of the questions that will need to be tackled. More studies need to be developed around CTCs present in early breast cancer, and their presence and usefulness should be correlated with clinicopathological data, and gene expression data derived from currently recommended breast cancer prognostic markers and tests, for eg: Mammaprint and Oncotype Dx (Krishnamurthy et al, 2010). CTCs have the potential of being established as a reliable prognostic or diagnostic biomarker for early breast cancer, progression to metastasis, response to treatment, and development of anti-metastatic drugs.…”
Section: Future Directions: Challenges and Applicationsmentioning
confidence: 99%